1310 Evaluation of facilitators training in improving the workplace environment using a participatory approach for primary prevention in mental health. (24th April 2018) - Yoshikawa, E; Yoshikawa, T; Takeuchi, Y; Sano, Y; Yuasa, A; Kogi, K
Abstract : Introduction: The efficacy of a training program conducted for learning actions taken by facilitators engaged in promoting workplace environment improvements using a participatory approach for primary prevention in mental health was studied. The study was aimed at clarifying the effects of the training program on learning their role in facilitating workplace-level improvement actions. Methods: We conducted a three-and-a-half-hour facilitators training program in Tokyo. The participants included 21 occupational health practitioners. After the training, we distributed a questionnaire (response rate: 95.2%) and studied the effects of the training program. The average years of experience of the respondents was 11.5±7.6 years, and the respondents included six persons who had experience in activities to improve their workplace environment. The relation between the level of understanding of the training contents and the respondents' level of confidence about the learning results was analysed by using a chi-squared test. Results: All the respondents answered that they could understand the significance of improving the workplace environment using a participatory approach as well as the role of a facilitator. They evaluated the content of the training as generally high and agreed with the need for taking action-oriented steps applying participatory methods. Concerning the level of confidence about supporting improvement activities, eight respondents (42%) replied 'very confident' or 'somewhat confident, ' and 11 (58%) 'somewhat unconfident' or 'not confident at all.' The chi-square test did not reveal any statistically significant difference between groups on either item. Conclusion: The facilitators training in promoting the participants' understanding concerning the significance of improving the workplace environment was confirmed effective by using a participatory approach. It has been suggested that, in order to enable the participants to effectively practice at their workplace what they learned from the training, it is important to provide a thorough follow-up after the training.2